A rare case of common arterial trunk with coarctation of the aorta: a case report. Issue 7 (28th June 2022) - Abdelaal, Mohamed; Dedieu, Nathalie
Abstract: Background: A common arterial trunk is a relatively uncommon type of congenital heart defect. The anomaly is caused by an incomplete conotruncal septation. Arch anomalies, such as interruption, are associated with 10–20% of cases. We present a rare case of common arterial trunk with coarctation of the aorta and patent ductus arteriosus (PDA). Case summary: A term baby who was discovered to have a murmur on examination, for evaluation of the murmur an echocardiography was performed on Day 2 of life, which revealed the diagnosis of a common arterial trunk and coarctation of the aorta. The baby was given prostaglandin and intubated. Due to his poor general condition, he underwent an emergency pulmonary artery branch banding. He needed another 5 days in the intensive care unit to be stabilized before undergoing full repair. Discussion: Our patient has a common arterial trunk with a tricuspid competent truncal valve. The trunk is subdivided further into ascending aorta and main pulmonary artery. The pulmonary artery provided two branches and a PDA that connected to the descending aorta. The aortic branching pattern was as usual, there was an area of tight coarctation and posterior shelf just after the origin of the left subclavian artery before the descending aorta–PDA junction. The presence of coarctation may be considered as the left side of the spectrum of morphological changes toward the formation of aortic arch interruption (Type 4 Van Praagh).